A Shrimp amongst Whales? Assessing South Korea's Regional-power Status - David Shim (German Institute of Global and Area Studies (GIGA), 2009)
Recent developments in South Korea's foreign and security policies as well as major structural adjustments in the military alliance between the United States and South Korea indicate a new self-understanding on the part of South Korea in terms of playing a more assertive role in regional and even global affairs. Alongside its involvement in the so-called Six-Party Talks - a multinational framework to disarm a nuclear North Korea-South Korea's civil-military engagement in Afghanistan, Iraq and Lebanon demonstrates that the government's foreign policy posture is not only focused on Northeast Asian affairs but is also intended to engage in other international security hot spots. However, although it has considerable material resources and capabilities - in neorealist terms constituting the power base of a state actor - South Korea is widely seen as a minor player in world politics. By means of a specific set of indicators - pretension, endowment, influence, recognition - this paper seeks to answer the question of whether South Korea is a regional power. The methodological approach used to evaluate its position will be based on analytical frameworks and typologies compiled from the literature on regional powers. Following the introduction of this approach, different concepts of the term regional power and the selection of the methodological instruments are presented. The subsequent section analyzes the selected set of indicators with regard to South Korea's potential status as a regional power. The concluding chapter evaluates the findings and raises further questions related to the re-gional-power concept. – – Eine Krabbe unter Walen? Eine Untersuchung zum Regionalmachtstatus Südkoreas. Jüngere Entwicklungen in der Außen- und Sicherheitspolitik Südkoreas sowie grundlegende Anpassungen in der Militärallianz mit den USA deuten auf ein neues Selbstverständnis, eine bedeutendere Rolle in regionalen und globalen Politikfragen zu übernehmen. Neben der Beteiligung an den so genannten Sechs-Parteien-Gesprächen, in denen über die Denuklearisierung der koreanischen Halbinsel verhandelt wird, zeigen die zivil-militärischen Engagements im Irak, in Afghanistan, im Libanon und am Horn von Afrika, dass die südkoreanische Außenpolitik nicht nur regional auf Nordostasien ausgerichtet ist, sondern auch auf die 'Hot Spots' der internationalen Sicherheitspolitik zielt. Das Land verfügt zwar über beträchtliche materielle Ressourcen und militärische Fähigkeiten - aus neorealistischer Sicht die Machtgrundlage eines Akteurs -, wird jedoch weitestgehend als unerheblicher Akteur in der internationalen Politik wahrgenommen. Anhand ausgewählter Indikatoren - Anspruch, Ausstattung, Einfluss und Anerkennung - wird in diesem Beitrag untersucht, ob Südkorea eine Regionalmacht ist. Das methodische Vorgehen stützt sich auf einen analytischen Rahmen, welcher der Literatur zu Regional- und mittleren Mächten entnommen wurde. Zunächst wird diese Typologie vorgestellt, danach werden verschiedene Konzepte des Begriffes 'Regionalmacht' herausgearbeitet und die methodischen Instrumente ausgewählt. Im Folgenden werden die Indikatoren Südkoreas auf dessen vermeintlichen Regionalmachtstatus geprüft. Abschließend werden die Ergebnisse im Hinblick auf das eingeführte Konzept von Regionalmacht bewertet, was weitere Forschungsfragen aufwirft.
Keywords: 300; regional power; South Korea; foreign and security policy; intersubjective understanding